Organizational factors that influence the success of IT projects - KHAN, REHAN AHMAD (2018)
The present document presents a comprehensive outlook of the influence of organizational factors on IT projects and their success. This research aimed at exploring the extent to which certain organizational factors, including organizational culture and management style, organizational structure, organizational communication, organizational process assets and enterprise environment factors, can influence the successful implementation and completion of IT projects. The paper is focused on how the variables used per organizational factor is correlated with real-life scenarios and experiences of different project management teams that have been through project success and project failures. The rationale behind selecting this research area as a point of focus is that IT projects are widely being implemented across organizations, and that implementing new Information Technologies is mandatory for organizations of today in order to gain competitive advantage and sustainability. Comprehensive literature review was conducted, involving multiple secondary sources, such as peer-reviewed journals, academic sources, organizational websites and periodicals. Primary data were collected and subjected to descriptive analysis, ANOVA and linear regression analysis. Hypotheses testing revealed an insignificant relationship between organizational culture and management styles, enterprise environmental factors and the success of IT projects. On the other hand, the research study revealed that organizational process assets, quality of organizational communication, organizational structure can serve as effective predictors for success of IT projects. Overall, the study could measure project success of IT projects through organizational factors. The reliable differences of sample data have determined that the organizational factors have a significant relationship in measuring project success.